Peran teknologi dalam manajemen strategi perbankan syariah di era ekonomi digital - Lamondo, Mohamad Safriyanto (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the role of technology in supporting the strategic management of Islamic banking in the digital economy era. Using qualitative methods through literature review, this study examines the impact of technologies such as AI, big data, blockchain, and fintech on operational efficiency, risk management, and product innovation in Islamic banking. The results of the study show that technology plays a significant role in improving process efficiency, expanding service access, and strengthening risk management by utilizing AI and blockchain which help ensure compliance with Islamic principles. However, Islamic banking also faces challenges such as cybersecurity, data protection, and adjusting Islamic regulations to ever-evolving technology.